What Happens after the `Daddy Months'? Fathers' Involvement in Paid Work, Childcare, and Housework after Taking Parental Leave in Germany - Mareike Bünning (European Sociological Review, 2015)
The German parental leave reform of 2007 created a new incentive for men to take parental leave by introducing `daddy months': 2 months of well-remunerated leave exclusively reserved for fathers. Against the backdrop of the reform, this study examines how fathers' uptake of parental leave affects the amount of time they spend on paid work, housework, and childcare after the leave has ended. It investigates whether the effect of parental leave differs by the length of leave taken and by whether fathers took the leave alone or at the same time as their partners. Using data from the German Socio-Economic Panel from 2006 to 2012 and Families in Germany from 2010 to 2012, the results of fixed-effects regressions indicate that fathers who took parental leave subsequently reallocated their time from work to home. They reduced their working hours and increased their involvement in childcare even after short and joint periods of parental leave. But only those who took >2 months of leave or were on leave while their partner was working subsequently increased their participation in housework. Hence, fathers increased their involvement in childcare already after short leaves, whereas enhanced gender equality in couples' division of labour especially emerged after longer or solo leaves.
Keywords: 330; father; gainful work; child care; housework; parental leave; Federal Republic of Germany; work-family balance; division of labor; gender-specific factors; public benefits; family policy